Balanced Nutrition Education for Women in the P2WKSS Program in Haurgeulis Village, Indramayu - Dedeh Husnaniyah; Riyanto Riyanto; Irda Novrida Ashar (Karya Kesehatan Siwalima, 2025)
The Program for Increasing the Role of Women Towards Healthy and Prosperous Families (P2WKSS) is one of the government's efforts to improve the quality of family life through women's empowerment. Women have a very important role in providing food and family health, so women ideally have good knowledge about balanced nutrition. The aim of this Community Service Activity is to provide education about balanced nutrition for women in the Women's Role Enhancement Program Towards a Healthy and Prosperous Family (P2WKSS) in Haurgeulis Village, Indramayu. The method for community service includes three stages, namely: the stage of analyzing the partner's situation and condition, the education stage and the evaluation stage. The results of this community service activity are an increase in knowledge about balanced nutrition for women in the Program for Increasing the Role of Women Towards Healthy and Prosperous Families (P2WKSS) in Haurgeulis Village, Indramayu, This program significantly improved women’s knowledge on balanced nutrition.